Anti-obesity effects of capsaicin and the underlying mechanisms: a review. Issue 9 (21st August 2020) - Li, Run; Lan, Yaqi; Chen, Chengyu; Cao, Yong; Huang, Qingrong; Ho, Chi-Tang; Lu, Muwen
Abstract : The mechanisms of anti-obesity effects of capsaicin in cell models, rodent models and human subjects were reviewed. Abstract : Obesity and overweight have become serious health problems in the world and are linked to a variety of metabolic disorders. Phytochemicals with a weight-loss effect have been widely studied for the past few decades. Capsaicin is the major bioactive component in red chili peppers with many beneficial functions. Its anti-obesity effects have been evaluated extensively using different model systems, including cell models, animal models and human subjects. In this paper, anti-obesity effects of capsaicin are reviewed and the underlying mechanisms are characterized.